Capillary pressure‐saturation relations in quartz and carbonate sands: Limitations for correlating capillary and wettability influences on air, oil, and supercritical CO2 trapping. Issue 8 (31st August 2016) - Wang, Shibo; Tokunaga, Tetsu K.; Wan, Jiamin; Dong, Wenming; Kim, Yongman
Abstract: Capillary pressure ( Pc )‐saturation ( Sw ) relations are essential for predicting equilibrium and flow of immiscible fluid pairs in soils and deeper geologic formations. In systems that are difficult to measure, behavior is often estimated based on capillary scaling of easily measured Pc – Sw relations (e.g., air‐water, and oil‐water), yet the reliability of such approximations needs to be examined. In this study, 17 sets of brine drainage and imbibition curves were measured with air‐brine, decane‐brine, and supercritical (sc) CO2 ‐brine in homogeneous quartz and carbonate sands, using porous plate systems under ambient (0.1 MPa, 23°C) and reservoir (12.0 MPa, 45°C) conditions. Comparisons between these measurements showed significant differences in residual nonwetting phase saturation, Snw, r . Through applying capillary scaling, changes in interfacial properties were indicated, particularly wettability. With respect to the residual trapping of the nonwetting phases, Snwr, CO2  >  Snwr, decane  >  Snwr, air . Decane‐brine and scCO2 ‐brine Pc – Sw curves deviated significantly from predictions assuming hydrophilic interactions. Moreover, neither the scaled capillary behavior nor Snw, r for scCO2 ‐brine were well represented by decane‐brine, apparently because of differences in wettability and viscosities, indicating limitations for using decane (and other organic liquids) as a surrogate fluid in studies intended to apply to geological carbon sequestration. Thus, challenges remain in applying scaling for predicting capillary trapping and multiphase displacement processes across such diverse fields as vadose zone hydrology, enhanced oil recovery, and geologic carbon sequestration. Key Points: Capillary pressure‐saturation relations and residual trapping for multiple fluid systems in quartz and carbonate media were studied Wettability alteration causes lower than expected capillary pressures and higher than expected residual trapping of decane and scCO2 Using surrogate fluid underpredicts residual trapping of scCO2 . Experiments with scCO2 remain necessary to measure capillary behavior